2019
DOI: 10.1534/g3.119.400609
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Contiguous Reference Genome for Northern Bobwhite (Colinus virginianus)

Abstract: Northern bobwhites (Colinus virginianus) are small quails in the New World Quail family (Odontophoridae) and are one of the most phenotypically diverse avian species. Despite extensive research on bobwhite ecology, genomic studies investigating the evolution of phenotypic diversity in this species are lacking. Here, we present a new, highly contiguous assembly for bobwhites using tissue samples from a vouchered, wild, female bird collected in Louisiana. By performing a de novo assembly and scaffolding the asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Long‐read sequencing data have been demonstrated to efficiently fill gaps in genome assemblies that are likely associated with structural variants, repeat regions or phasing errors (Morgan et al., 2022; Salter et al., 2019). We, however, showed that after de novo assembly using long‐read Pacbio data, polishing using Illumina short‐read data and reconstructing polymorphic diploid assembly to a haploid sub‐assembly, the genome assembly of D. maya had an N50 = 17.1 Mb, with the longest scaffold = 59 Mb (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Long‐read sequencing data have been demonstrated to efficiently fill gaps in genome assemblies that are likely associated with structural variants, repeat regions or phasing errors (Morgan et al., 2022; Salter et al., 2019). We, however, showed that after de novo assembly using long‐read Pacbio data, polishing using Illumina short‐read data and reconstructing polymorphic diploid assembly to a haploid sub‐assembly, the genome assembly of D. maya had an N50 = 17.1 Mb, with the longest scaffold = 59 Mb (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…The full procedure is described in the Supplemental Methods in Data S1. We aligned reads to the bobwhite reference genome (Salter et al, 2019) using bwa v0.7.17 (Li & Durbin, 2009) and samtools v1.10 (Li et al, 2009), and we called SNPs using a parallel implementation of the Best Practices for Variant Discovery (Salter & Faircloth, 2021; Van der Auwera & O'Connor, 2020) in GATK v4.1.9.0, including base quality score recalibration (McKenna et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The full procedure is described in the Supplemental Methods. We aligned reads to the bobwhite reference genome (56) using bwa v0.7.17 (57) and samtools v1.10 (58), and we called SNPs using a parallel implementation of the Best Practices for Variant Discovery (59, 60) in GATK v4.1.9.0, including base quality score recalibration (61).…”
Section: Methodsmentioning
confidence: 99%